2010
DOI: 10.1007/s00464-010-1348-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative versus intraoperative endoscopic sphincterotomy for management of common bile duct stones

Abstract: PES/LC and LC/IOES are both good options for dealing with preoperatively diagnosed CBDS, but when there is enough experience and facilities, LC/IOES, as a single-stage treatment, would be preferable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 51 publications
1
79
0
3
Order By: Relevance
“…The CBD stone removal was performed after cholecystectomy by turning the patient to prone position as is done normally for routine ERC. We concur with these authors [17] that passing the guide-wire through cystic duct offers no added advantage and the bowel distention resulting from ERC renders the subsequent steps of cholecystectomy cumbersome. In a review of 27 published studies on the rendezvous technique comprising of 795 patients, Greca et al reported a success rate of 92.3 %, morbidity 5.1 % and the mortality rate 0.37 %.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The CBD stone removal was performed after cholecystectomy by turning the patient to prone position as is done normally for routine ERC. We concur with these authors [17] that passing the guide-wire through cystic duct offers no added advantage and the bowel distention resulting from ERC renders the subsequent steps of cholecystectomy cumbersome. In a review of 27 published studies on the rendezvous technique comprising of 795 patients, Greca et al reported a success rate of 92.3 %, morbidity 5.1 % and the mortality rate 0.37 %.…”
Section: Discussionsupporting
confidence: 83%
“…This single-sitting approach was subsequently termed as 'rendezvous' technique [16]. We followed a slightly different technique similar to what has been reported by ElGeidie et al [17]. The CBD stone removal was performed after cholecystectomy by turning the patient to prone position as is done normally for routine ERC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed et al [10] compared preoperative versus intraoperative endoscopic sphincterotomy for management of CBD stones. 198 patients diagnosed preoperatively with gallbladder and CBD stones were eligible.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There are only a few randomized trials available comparing the single stage with sequential management (ERCP followed by LC) of patients with concomitant gallstones and CBD stones [8,9]. Combined single stage laparoendoscopic approach to the management of choledocholithiasis has also been advocated by established centres [1,10] with results comparable to sequential management and single stage total laparoscopic exploration.…”
Section: Introductionmentioning
confidence: 99%